Diagnosis of Intoxication by the Organophosphate VX: Comparison Between an Electrochemical Sensor and Ellman´s Photometric Method - Pohanka, Miroslav; Hrabinova, Martina; Kuca, Kamil (Sensors (Basel, Switzerland), 2008)
An electrochemical sensor is introduced as a tool applicable for diagnosis of intoxication by cholinesterase inhibitors caused by the well-known nerve agent VX. The traditional Ellman method was chosen for comparison with the sensor's analytical parameters. Both methods are based on estimation of blood cholinesterase inhibition as a marker of intoxication. While Ellman´s method provided a limit of detection of 5.2´10-7 M for blood containing VX, the electrochemical sensor was able to detect 4.0´10-7 M. Good correlation between both methods was observed (R = 0.92). The electrochemical sensor could be considered a convenient tool for a fast yet accurate method, easily available for field as well as laboratory use. Time and cost savings are key features of the sensor-based assay.
Keywords: biosensor; carbamate; Organophosphate; intoxication; diagnosis